2007
DOI: 10.4049/jimmunol.178.2.936
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoke Impairs NK Cell-Dependent Tumor Immune Surveillance

Abstract: In this study, we investigated the impact of cigarette smoke on tumor immune surveillance and its consequences to lung tumor burden in a murine lung metastasis model. Cigarette smoke exposure significantly increased the numbers of lung metastases following B16-MO5 melanoma challenge. This effect was reversible; we observed significantly fewer tumor nodules following smoking cessation. Using RAG2−/− and RAG2−/−γc−/− mice, we provide strong evidence that increased tumor incidence was NK cell dependent. Furthermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
74
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 39 publications
7
74
0
Order By: Relevance
“…To date, the role of NK cells in the pathogenesis of lung fibrosis remains unclear, and their involvement in this process in the context of autoimmune diseases, including aSS, is not known. Some studies have reported reduced NK cell function in diseases leading to idiopathic pulmonary fibrosis, through the lack of interactions of NK cells with epithelial cells or collagenproducing cells (34,35). Some animal models also suggested that NK cells could prevent lung fibrosis, through the production of IFN-g (36).…”
Section: Discussionmentioning
confidence: 99%
“…To date, the role of NK cells in the pathogenesis of lung fibrosis remains unclear, and their involvement in this process in the context of autoimmune diseases, including aSS, is not known. Some studies have reported reduced NK cell function in diseases leading to idiopathic pulmonary fibrosis, through the lack of interactions of NK cells with epithelial cells or collagenproducing cells (34,35). Some animal models also suggested that NK cells could prevent lung fibrosis, through the production of IFN-g (36).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that CS may impair NK cell function, leading to enhanced tumor burden following tumor challenge (58). Unfortunately, this report relied on the use of heterogeneous cell populations, so the contribution of NK cells remains undefined (58). The limited knowledge on NK cell function in COPD and the apparent dichotomy of results further highlight the need for more studies.…”
Section: Discussionmentioning
confidence: 99%
“…The only report directly examining NK cell function in COPD used cells derived from patients using inhaled steroids (56), a variable known to impair functional assays, particularly in COPD (57). It has also been suggested that CS may impair NK cell function, leading to enhanced tumor burden following tumor challenge (58). Unfortunately, this report relied on the use of heterogeneous cell populations, so the contribution of NK cells remains undefined (58).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the definition of a healthy smoker refers to an asymptomatic smoker with normal lung function values, even if respiratory bronchiolitis is present. Oxidative stress, increased epithelial apoptosis and deregulated immune responses represent well known smoking induced mechanisms [14][15][16][17][18][19][20][21]. It is known that cigarette smoking causes inflammatory cell recruitment, mostly macrophages, which have reduced apoptosis and increased survival.…”
Section: Is Smoking Related To the Pathogenesis Of Ilds?mentioning
confidence: 99%